Hispanic Migrant Farm Workers' Attitudes Toward Mobile Phone-Based Telehealth for Management of Chronic Health Conditions - Price, Matthew; Williamson, Deborah; McCandless, Romina; Mueller, Martina; Gregoski, Mathew; Brunner-Jackson, Brenda; Treiber, Eveline; Davidson, Lydia; Treiber, Frank (JMIR Publications, 2013)
BackgroundMobile phone-based interventions present a means of providing high quality health care to hard-to-reach underserved populations. Migrant farm workers (MFWs) are among the most underserved populations in the United States due to a high prevalence of chronic diseases yet limited access to health care. However, it is unknown if MFWs have access to mobile phone devices used in mobile health (mHealth) interventions, or if they are willing to use such technologies. ObjectiveDetermine rates of ownership of mobile devices and willingness to use mHealth strategies in MFWs. MethodsA demonstration of mHealth devices and a survey were individually administered to 80 Hispanic MFWs to evaluate use of mobile phones and mHealth devices and willingness to use such technologies. ResultsOf the 80 participants, 81% (65/80) owned cell phones capable of sending and receiving health-related messages. Most participants (65/80, 81%) were receptive to using mHealth technology and felt it would be helpful in enhancing medication adherence, self-monitoring health conditions, and receiving quicker medication changes from their doctors (median scores ≥4 on 5-point Likert scales). Relations between age and attitudes toward using mHealth were not statistically significant. ConclusionsHispanic MFWs have access to mobile phones and are willing to use mHealth devices. Future work is needed to comprehensively evaluate the degree to which these devices could be used.